A case study on design and manufacture of tilting pad thrust bearing for steam turbine of fertilizer factories - Amin, A. K. M. Nurul; M. M., Rahman; M. M., Hossain (1996)
Bangladesh has to depend mainly on imported spare parts for maintenance of its major industries. The picture is not different in the case of the fertilizer factories. Tilting pad thrust bearing is a critical and very expensive spare part of fertilizer factories. Like many other spares this spare has to be imported because it is not locally manufactured. The country is loosing a huge amount of foreign currency in importing this and other spare parts. Apart from the high procurement cost import involves long lead time. In order to avoid factory shut downs a lot of spares are also kept in reserve. This leads to very high inventory costs which results in high factory overhead costs. As an attempt to solve these problems the present study was under taken. The main objective of the work was to ascertain whether local manufacture of a critical spare parts like tilting pad thrust bearing was at all feasible. Design and manufacture of the above mentioned bearing were performed under the present case study. Tests were performed to identify the material of the bearing lobes as well as the composition of the of the white metal layer. Since no working or detail drawing of the part was available in the factory, the different dimensions of the spare part were determined by precision measurements and by analytical methods. Apart from that the sequence of manufacturing operations were so designed as to permit its manufacturing using local facilities. Fixtures required for maintaining the required precision of manufacturing were designed appropriately. The part was subsequently manufactured using technical facilities of BUET and BITAC. The lobes were precisely machined and then white metalling was performed. The bearing lobes were then ground and polished to accurate dimensions. Finally the jobs were checked for quality and are ready for practical tests.